Variation in Plastome Sizes Accompanied by Evolutionary History in Monogenomic Triticeae (Poaceae: Triticeae) - Chen, Ning; Sha, Li-Na; Wang, Yi-Ling; Yin, Ling-Juan; Zhang, Yue; Wang, Yi; Wu, Dan-Dan; Kang, Hou-Yang; Zhang, Hai-Qin; Zhou, Yong-Hong; Sun, Gen-Lou; Fan, Xing (Frontiers in Plant Science, 2021)
To investigate the pattern of chloroplast genome variation in Triticeae, we comprehensively analyzed the indels in protein coding genes and intergenic sequence, gene losses/pseudonization, intron variation, expansions/ contractions in inverted repeat regions, and the relationship between sequence characteristics and chloroplast genome size in 34 monogenomic Triticeae plants. Ancestral genome reconstruction suggests that the major length variations occurred in four stem branches of monogenomic Triticeae followed by independent changes in each genus. It was shown that the chloroplast genome sizes of monogenomic Triticeae were highly variable. The chloroplast genome of Pseudoroegneria, Dasypyrum, Lophopyrum, Thinopyrum, Eremopyrum, Agropyron, Australopyrum, and Henradia in Triticeae had evolved towards size reduction, largely due to pseudogenes elimination events and length deletion fragments in intergenic. Aegilops/Triticum complex, Taeniatherum, Secale, Crithopsis, Herteranthelium and Hordeum in Triticeae had larger chloroplast genome size. The large size variation in major lineages and their subclades are most likely the consequences of adaptive processes, since those variations were significantly correlated with divergence time and historical climatic changes. We also found several intergenic regions, such as petN-trnC, psbE-petL, contain the unique genetic information, which can be used as important tools to identify the maternal relationship among Triticeae species. Our results contribute to the novel knowledge of plastid genome evolution in Triticeae.